Global Insights on Future Trends of Hybrid/EV Driveline Lubrication and Thermal Management - Tung, Simon C.; Woydt, Mathias; Shah, Raj (Frontiers in Mechanical Engineering, 2020)
Global automotive industries have recently switched development trends from the traditional powertrain mechanical components into the digital transformation of the electrification components in advanced propulsion vehicles. This industrial impact on global development trend into automotive electrification designs has created an emerging technology for new propulsion systems such as hybrid electrical vehicles (HEV) or electrical vehicles (EV). Advanced propulsion systems rising from global guidelines are meant to improve vehicle fuel efficiency and minimize pollution emissions from transportation vehicles. In many HEV or EV advanced system designs, automotive lubricants such as drivetrain fluids or thermal coolants comes into contact with the integrated electric motor (e-motor) and thermal management devices. This leads to the addition of electrical and thermal properties, which must be taken into account on top of conventional lubricant properties. The introduction of electrification components has been targeted for energy efficiency and long-term durability. Automotive industries have asked for the implementation of specialized automotive lubricants or driveline fluids to allow for appropriate thermal cooling specifications, present bearing protection, ensure corrosion protection, and offer oxidation and sludge control. This review paper will provide with global insights on future automotive electrification growth trends with respect to innovative driveline lubricants and thermal cooling liquids used in Hybrid/EV vehicles. Coming research activities in innovative driveline fluids will be focused on minimizing friction loss and maximizing hybrid component durability. The major goal of this paper is to underline the future electrification development trends and the required lubricants for advanced Hybrid/EV vehicles. The major section of this paper will be focused on the most important progress of automotive lubrication in the areas of energy conversion effectiveness, driveline trustworthiness, cooling system design and thermal management control. In this review paper, new developments in thermal management fluids have been described to help promote the high-performance cooling system on electrical batteries, motors, and power electronics. In addition, global research activities using novel nanofluids for thermal cooling have the high potential for application to EV/Hybrid technologies. This paper has reviewed the state-of-art thermal management technology used for extending driving range and durability of EV/Hybrid vehicles. At the end of this paper, using high promising nanofluids for thermal cooling in fuel cell components will be illustrated to demonstrate this potential application in EV/Hybrid vehicles.